A Novel Nomogram for Predicting the Risk of Pneumonia After Intracerebral Hemorrhage - Sun Y; Zhang L; Huang B; He Q; Hu B (Journal of Inflammation Research)
Yuanyuan Sun,* Lei Zhang,* Baisong Huang, Quanwei He, Bo Hu Department of Neurology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quanwei He; Bo Hu, Department of Neurology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 Jiefang Avenue, Wuhan , 430022, People’s Republic of China, Tel +8613554111043 ; +8613707114863, Email hequanwei2008@126.com; hubo@mail.hust.edu.cnBackground: Pneumonia is among the most dangerous complications of infection after intracerebral hemorrhage. We aimed to create a novel nomogram for pneumonia after intracerebral hemorrhage.Methods and Results: The data from the Chinese Cerebral Hemorrhage: Mechanism and Intervention (CHEERY) study was analyzed. Thirty percent of qualified patients were placed in the validation group (n=763) while seventy percent of them were randomly placed in the training group (n=1784). In the multivariate analysis, ten variables were included in the model: age (β= 0.023, P< 0.001), hospital days (β=0.392, P< 0.001), baseline mRS score (β=0.484, P< 0.001), baseline GCS score (β=− 0.285, P< 0.001), hs-CRP (β=0.328, P< 0.001), hematoma volume (β=0.376, P< 0.001), brainstem hemorrhage (β=0.956, P=0.002), intraventricular hemorrhage (β=0.629, P=0.001), and β-blocker (β=0.899, P< 0.001) In the training subset, the areas under curve were 0.805 (95% CI, 0.773– 0.833). The model was subsequently examined in the validation group, with the area under curve 0.767 (95% CI, 0.716– 0.807). There was strong agreement between the anticipated and actual survival rates in the nomogram calibration curves for both the training and validation groups. The clinical value of the model is assessed by means of Decision Curve Analysis. In addition, we validated other models with this cohort, which showed that our model had better discrimination. Moreover, the area under the curve of the catboost model established using the above nine variables in the training set and the validation set is 0.87(95% CI, 0.80– 0.90) and 0.77(95% CI, 0.72– 0.80).Conclusion: We have established a simple and easy predictive tool. By evaluating the incidence of pneumonia after intracerebral hemorrhage, we can identify high-risk groups early. At the same time, our study also suggests that doctors should be cautious in the use of β-blocker in clinical decision-making.Keywords: pneumonia, inflammation, intracerebral hemorrhage, nomogram, β-blocker